1999
DOI: 10.2307/3871054
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis abi1-1 and abi2-1 Phosphatase Mutations Reduce Abscisic Acid-Induced Cytoplasmic Calcium Rises in Guard Cells

Abstract: Elevations in cytoplasmic calcium ([Ca(2)+](cyt)) are an important component of early abscisic acid (ABA) signal transduction. To determine whether defined mutations in ABA signal transduction affect [Ca(2)+](cyt) signaling, the Ca(2)+-sensitive fluorescent dye fura 2 was loaded into the cytoplasm of Arabidopsis guard cells. Oscillations in [Ca(2)+](cyt) could be induced when the external calcium concentration was increased, showing viable Ca(2)+ homeostasis in these dye-loaded cells. ABA-induced [Ca(2)+](cyt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(218 citation statements)
references
References 0 publications
17
201
0
Order By: Relevance
“…In microsomal membranes of V. faba guard cells, both H 1 -ATPase properties were also reduced by micromolar concentrations of Ca 21 , the inhibitory effect of Ca 21 being reversed by the addition of the Ca 21 chelator BAPTA (Kinoshita et al, 1995). Allen et al (1999) reported that anion channel activation by ABA could be mimicked by an external application of Ca 21 , indicating that such an activation was Ca 21 -dependent in Arabidopsis guard cells. Here, we confirmed in Arabidopsis cell suspensions this result by an opposite approach.…”
Section: Ca 21 Has a Dual Effect Leading To Plasma Membrane Depolarizmentioning
confidence: 98%
“…In microsomal membranes of V. faba guard cells, both H 1 -ATPase properties were also reduced by micromolar concentrations of Ca 21 , the inhibitory effect of Ca 21 being reversed by the addition of the Ca 21 chelator BAPTA (Kinoshita et al, 1995). Allen et al (1999) reported that anion channel activation by ABA could be mimicked by an external application of Ca 21 , indicating that such an activation was Ca 21 -dependent in Arabidopsis guard cells. Here, we confirmed in Arabidopsis cell suspensions this result by an opposite approach.…”
Section: Ca 21 Has a Dual Effect Leading To Plasma Membrane Depolarizmentioning
confidence: 98%
“…Dominant negative mutations in PP2C-type protein phosphatases abi1 and abi2 disrupt ABA-activation of Ca 2+ channels [17,124]. ROS production was also disrupted in the abi1-1 mutant but not in the abi2-1 mutant, leading to the hypothesis that abi2-1 affects responses downstream of ROS production [17] and abi1-1 affects responses upstream of ROS production (Fig.…”
Section: Ca 2+ Channels: Roles In Guard Cell Signal Transductionmentioning
confidence: 99%
“…abo6 was also crossed with abi1-1and abi2-1 and the double mutants were identified (Allen et al, 1999).…”
Section: Genetic Mapping and Mutant Complementationmentioning
confidence: 99%